2022
DOI: 10.3389/fpsyg.2022.856750
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of patients' satisfaction and trust toward healthcare service environment in general practice clinics

Abstract: This study aimed to examine the healthcare service environment, patients' experience, and responses toward healthcare services in private general practice (GP) clinics. Self-administered questionnaires were used for collecting data from 367 respondents with prior experience in visiting the general practice clinics in Malaysia. SmartPLS statistical tool was used to test the underlying hypotheses. The results revealed that ambiance, service delivery, interior decor, and cleanliness had a significant influence on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 80 publications
1
24
0
Order By: Relevance
“…The independent variables used as control variables are chosen in accordance to the specifications of previous research on trust, the informal economy and informal payments for health services ( Balabanova and McKee, 2002 ; Szende and Culyer, 2006 ; Tomini and Maarse, 2011 ; Tomini et al, 2012a , b ; Baji et al, 2013 ; Kaitelidou et al, 2013 ; Tomini and Groot, 2013 ; Riklikiene et al, 2014 ; Arsenijevic et al, 2015 ; Danyliv et al, 2015 ; Stepurko et al, 2015 ; Williams et al, 2016 ; Ai et al, 2022 ; Horodnic et al, 2022a ) and include: age, gender, educational level, income, employment status, residence area (rural or village) (details in Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The independent variables used as control variables are chosen in accordance to the specifications of previous research on trust, the informal economy and informal payments for health services ( Balabanova and McKee, 2002 ; Szende and Culyer, 2006 ; Tomini and Maarse, 2011 ; Tomini et al, 2012a , b ; Baji et al, 2013 ; Kaitelidou et al, 2013 ; Tomini and Groot, 2013 ; Riklikiene et al, 2014 ; Arsenijevic et al, 2015 ; Danyliv et al, 2015 ; Stepurko et al, 2015 ; Williams et al, 2016 ; Ai et al, 2022 ; Horodnic et al, 2022a ) and include: age, gender, educational level, income, employment status, residence area (rural or village) (details in Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Hoshin kanri (goal-oriented) is a means of getting and sealing strategic goals and having an insight about the future to build up people. Failure to set healthcare goals leads an organization to terrible performance outcomes and may also lower the productivity and motivation of staff (Ljungblom, 2012;Ai et al, 2022;Al Mamun et al, 2022). Mahmoud et al (2021) reported that although lean management practices are used in the healthcare sector, however, their impacts on staff have not been synthesized.…”
Section: Hoshin Kanrimentioning
confidence: 99%
“…Besides, it is regarded as the involvement and interaction of employees regarding job opinions and ides which help to achieve the organizational objectives and target (Van Dyne & LePine, 1998). However, employees' voice is the essential source of information which provides pleasures to develop individuals and organization performance (Detert & Burris, 2007;Ai et al, 2022). Moreover, employee voice is considered as the opportunity to express views, opinions, and ideas with the management of an organization which directly impact on employee performance.…”
Section: Employee Voicementioning
confidence: 99%